Pengaruh Kualitas Layanan terhadap Loyalitas Konsumen melalui Variabel Intervening Kepuasan Konsumen pada Warung Kelontong di Kecamatan Banjarmasin Timur - Fanlia Prima Jaya; Gusti Suryasari R (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2017)
type of research is explanatory research that aims to explain the causal relationship between variables through hypothesis testing and is also a conclusive research. The population of this study was overall Consumers who use the Convenience Store in Kecamatan BanjarmasinTimur, that as many as 118.429 people. The results of this study indicate that the results of validity and reliability of all the variables are significantly related and reliable. Classic assumption test consisting of Multicollinearity test, test heterocedastity, Autokolerasi test, normality test showed no irregularities. After linear regression analysis consisting of t-test and Anova it can be concluded that the Service Quality and Consumers Satisfaction as intervening simultaneously significant effect on Consumers Loyalty at Convenience Store in Kecamatan BanjarmasinTimur, The size of the effect can be seen from the coefficient terminated or R2 = 0.297.Keywords :Service Quality,Consumers Satisfaction, Consumers Loyalty.